Comparison of 20nm silver nanoparticles synthesized with and without a gold core: Structure, dissolution in cell culture media, and biological impact on macrophages - Munusamy,P; Wang,C; Engelhard,MH; Baer,DR; Smith,JN; Liu,C; Kodali,V; Thrall,BD; Chen,S; Porter,AE; Ryan,MP (Biointerphases, 2015)
Widespread use of silver nanoparticles raises questions of environmental and biological impact. Many synthesis approaches are used to produce pure silver and silver-shell gold-core particles optimized for specific applications. Since both nanoparticles and silver dissolved from the particles may impact the biological response, it is important to understand the physicochemical characteristics along with the biological impact of nanoparticles produced by different processes. The authors have examined the structure, dissolution, and impact of particle exposure to macrophage cells of two 20 nm silver particles synthesized in different ways, which have different internal structures. The structures were examined by electron microscopy and dissolution measured in Rosewell Park Memorial Institute media with 10% fetal bovine serum. Cytotoxicity and oxidative stress were used to measure biological impact on RAW 264.7 macrophage cells. The particles were polycrystalline, but 20 nm particles grown on gold seed particles had smaller crystallite size with many high-energy grain boundaries and defects, and an apparent higher solubility than 20 nm pure silver particles. Greater oxidative stress and cytotoxicity were observed for 20 nm particles containing the Au core than for 20 nm pure silver particles. A simple dissolution model described the time variation of particle size and dissolved silver for particle loadings larger than 9 μg/ml for the 24-h period characteristic of many in-vitro studies.